STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT SUKU PAMONA DI DESA BUYUMPONDOLI, KECAMATAN PAMONA PUSELEMBA, KABUPATEN POSO, SULAWESI TENGAH - Kurniawan P. Bandjolu; Orryani Lambui; Ramadanil Ramadanil (Biocelebes, 2019)
The objectives of this study was to determine value of plants for Pamona community and to identify plant species that used traditionally as medicine. The method was survey method by using direct interview to thirteen (13) respondents. The number of respondents was determined by purposive and snow ball technique sampling. We recorded that there were thirty two (32) species of plant that used by Pamona community as medicine. Based on plant organ, the Pamona community used fruit 3 species, leaf 22 species, stem 4 species, rhizome 2 species and fruit skin 1 species.